2021
DOI: 10.1016/j.aimed.2021.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and complementary medicine use and beliefs during COVID-19 outbreak: A cross-sectional survey among the general population in Turkey

Abstract: Objective Coronavirus disease 2019 (COVID-19) caused a universal psychosocial impact and individuals exposed to threats prefer to try self-care interventions and adhere to non-conventional approaches such as traditional and complementary medicine (T&CM) for preventive purposes. This study was conducted to determine the use and belief about T&CM among the general population during the COVID-19 outbreak. Method A cross-sectional online survey wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 31 publications
2
24
2
1
Order By: Relevance
“…In Turkey, a cross-sectional survey study was conducted among 389 participants wherein 153 (39.3%) participants reported to have used traditional and complementary medicine during COVID-19, especially, as herbal medicines and nutritional supplements such as vitamins [ 61 ]. Medicinal plants such as Rosa canina L., Mentha × piperita L., Sambucus nigra L., Olea europaea L., Eucalyptus spp ., Melissa officinalis L., and Origanum vulgare L. have been used in Turkish folk medicine for centuries to treat flu and have been suggested for potential use in COVID-19 treatment [ 91 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…In Turkey, a cross-sectional survey study was conducted among 389 participants wherein 153 (39.3%) participants reported to have used traditional and complementary medicine during COVID-19, especially, as herbal medicines and nutritional supplements such as vitamins [ 61 ]. Medicinal plants such as Rosa canina L., Mentha × piperita L., Sambucus nigra L., Olea europaea L., Eucalyptus spp ., Melissa officinalis L., and Origanum vulgare L. have been used in Turkish folk medicine for centuries to treat flu and have been suggested for potential use in COVID-19 treatment [ 91 ].…”
Section: Main Textmentioning
confidence: 99%
“…In Turkey, a cross-sectional survey study was conducted among 389 participants wherein 153 (39.3%) participants reported to have used traditional and complementary medicine during COVID-19, especially, as herbal medicines and nutritional supplements such as vitamins [61].…”
Section: Turkish Ethnomedicinal Plants In Covid-19 Healthcarementioning
confidence: 99%
“…Moreover, the advantages of the integration of Chinese herbal medicine with conventional medicine are increase the cure rate and reduce the illness severity, hospital stay and mortality rate of COVID-19 cases, which have been indicated in previous studies [9] . The universal psychosocial impact caused by COVID-19 has led to raising panic and fear among the general population, with many individuals have preferred to try non-conventional therapies such as complementary medicine [10] , [11] , [12] . The recent cross- sectional study in Turkey proved the tendency of applying traditional and complementary medicine among general population, So, that almost 40% of the participants reported the usage of the traditional and complementary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…The recent cross- sectional study in Turkey proved the tendency of applying traditional and complementary medicine among general population, So, that almost 40% of the participants reported the usage of the traditional and complementary medicine. A significant proportion of believed that these modalities have fewer side-effects, are effective, and should be used for managing COVID-19 [12] . Another research in Iran indicated that 84% of general population applied at least one type of complementary and alternative medicine during the COVID-19 pandemic [13] .…”
Section: Introductionmentioning
confidence: 99%
“…As we near the end of the second year of the COVID-19 pandemic, the impact of traditional, complementary and integrative health (TCIH) on COVID-19, and the impact of COVID-19 on TCIH, has been a focus of the journal. In this issue alone, we have multiple articles examining the way that TCIH practitioners and practices have adapted and evolved to meet the challenges of the pandemic [33] , [34] , [35] . Last year we published a special issue which included a series of articles examining the evidence for the potential role of traditional, complementary and integrative treatments in addressing COVID-19 [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , as well as a guide to assist others critically appraise future studies of TCIM interventions [12] .…”
mentioning
confidence: 99%